2020
DOI: 10.3897/nucet.6.57742
|View full text |Cite
|
Sign up to set email alerts
|

Neutronic modeling of a subcritical system with corium particles and water (from international benchmark)

Abstract: After the accident at the Fukushima Daiichi NPP, the attention of the scientific community is riveted on how the consequences are being eliminated. Removing corium – a lava-like resolidified mixture of nuclear fuel with other structural elements of the reactor – remains the most difficult task, the solution of which can take several decades. It is extremely important to exclude the occurrence of any emergency processes during the removal of corium. The purpose of this work was to solve a coordinated hydrodynam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…There is no significant difference between eigenvalues obtained with all three codes. This is a current research progress since paper [7] that reported MCU results differing by more than a percentage point for 0.1 s timepoint. Improvement of the results was achieved by correcting calculation model in MCU.…”
Section: Effective Multiplication Factormentioning
confidence: 94%
See 1 more Smart Citation
“…There is no significant difference between eigenvalues obtained with all three codes. This is a current research progress since paper [7] that reported MCU results differing by more than a percentage point for 0.1 s timepoint. Improvement of the results was achieved by correcting calculation model in MCU.…”
Section: Effective Multiplication Factormentioning
confidence: 94%
“…This article continues a series of papers in which detailed benchmark description and results of preliminary explicit effective multiplication factor calculations were presented [7,8], and also developed programming tool for visualizing the calculation results was introduced [9]. Current paper focuses on more accurate calculation results of several parameters such as neutron fluxes, reaction rates, and relative FOM (Figure of Merit) as well as improved effective multiplication factor calculation results (results improvement was achieved by correcting calculation model in MCU).…”
Section: Introductionmentioning
confidence: 96%
“…The CFD solver, DEM solvers, and the sub-models for evaluating momentum/energy exchange between fluid-particle phases were executed via the commercial code of STAR-CCM+ (Version 2020.3) [32], a general-purpose tool allowing the processing of three-dimensional calculation among multi-phases with high fidelity and flexibility. The MCN solver can be conducted on the in-house code of MVP3, developed by the JAEA [33] and validated via conducting benchmarking on the debris particles system with two other Monte-Carlo-based codes (Serpent and MCU), showing that the three modern codes are capable of performing neutronic analysis for the fuel debris particles system without significant discrepancy and with high accuracy [34]. The interface, which is liable for exchanging information and the workflow control between STAR-CCM+ and MVP3, was originally created in this research to realize the automated multi-physics-concerning function in the coupled CFD-DEM-MCN solver.…”
mentioning
confidence: 99%